An Unusual Case of Painful Phantom-Limb Sensations During Regional Anesthesia. Issue 2 (1st March 2004) - Paqueron, Xavier; Lauwick, Séverine; Le Guen, Morgan; Coriat, Pierre
Abstract : Objective: The objective of this article is to describe a late-onset phantom-limb pain during a continuous analgesic popliteal nerve block after foot surgery and its alleviation and recurrence when stopping and resuming the local anesthetic infusion. Case Report: A 29-year-old woman undergoing a left hallux valgus repair received a continuous popliteal sciatic nerve block for postoperative analgesia. Postoperatively, 6 hours after the commencement of a ropivacaine 0.2% infusion, she reported feelings of tingling, clenching pain, and missing-limb sensation below the ankle. The surgical site remained painless. Sensation elicited by touch and propioception were normally perceived. Only sensations for pinprick and heat were impaired. The ropivacaine infusion was stopped, followed 2.5 hours later by the complete regression of any abnormal sensation. Meanwhile, pain at the surgical site was scored at 50 mm on a 100-mm visual analogic scale. As the infusion of ropivacaine was resumed, the abnormal sensations reappeared. The catheter was removed, and abnormal sensations again disappeared. The patient was discharged from hospital without further complications. Conclusions: This observation suggests that phantom-limb pain can be of late-onset and might occur during a continuous infusion of low-concentration local anesthetic responsible only for an analgesic block, as shown by the fact that only thermal and pinprick sensations, known to depend on Aδ-fibers and C-fibers, were altered. Therefore, this case contradicts the usual belief that a profound block is necessary to elicit phantom-limb pain.